Expression Pattern and Ligand Binding Characteristics Analysis of Chemosensory Protein SnitCSP2 from Sirex nitobei - Pingping Guo; Enhua Hao; Han Li; Xi Yang; Pengfei Lu; Haili Qiao (Insects, 2023)
Sirex nitobei is an important wood-boring wasp to conifers native to Asia, causing considerable economic and ecological damage. However, the current control means cannot achieve better efficiency, and it is expected to clarify the molecular mechanism of protein–ligand binding for effective pest control. This study analyzed the expression pattern of CSP2 in S. nitobei (SnitCSP2) and its features of binding to the screened ligands using molecular docking and dynamic simulations. The results showed that SnitCSP2 was significantly expressed in female antennae. Molecular docking and dynamic simulations revealed that SnitCSP2 bound better to the host plant volatile (+)-α-pinene and symbiotic fungal volatiles terpene and (−)-globulol than other target ligands. By the molecular mechanics Poisson–Boltzmann surface area (MM-PBSA) method, the free binding energies of the three complexes were calculated as −44.813 ± 0.189 kJ/mol, −50.446 ± 0.396 kJ/mol, and −56.418 ± 0.368 kJ/mol, and the van der Waals energy was found to contribute significantly to the stability of the complexes. Some key amino acid residues were also identified: VAL13, GLY14, LYS61, MET65, and LYS68 were important for the stable binding of (+)-α-pinene by SnitCSP2, while for terpenes, ILE16, ALA25, TYR26, CYS29, GLU39, THR37, and GLY40 were vital for a stable binding system. We identified three potential ligands and analyzed the interaction patterns of the proteins with them to provide a favorable molecular basis for regulating insect behavioral interactions and developing new pest control strategies.